AB0609 NAILFOLD VIDEO CAPILLAROSCOPY AS A POTENTIAL DIAGNOSTIC TOOL IN SYSTEMIC VASCULITIS. (June 2019) - Rimar, Doron; Ingegnoli, Francesca; Rimar, Ori; Rosner, Itzhak; Rosenbaum, Michael; Kaly, Lisa; Boulman, Nina; Awisat, Abid; Slobodin, Gleb
Abstract : Background: Vasculitides are formally classified by artery size: large, medium or small, yet some overlap is evident as in Takayasu, a large vessel vasculitis manifesting also in retinal arterioles. Nailfold videocapillaroscopy (NVC) enables us to inspect changes in microvasculature. Only several small uncontrolled case series of light capillary microscopy in adult patients with vasculitis were reported in the literature, describing avascular areas and microhemorrhages in granulomatosis with polyangiitis (GPA) patients [1-2] and in [4] Behcet disease, and thin and tortuous capillaries in Takayasu arteritis [5]. Objectives: To characterize nailfold capillary changes by NVC in patients with autoimmune vasculitis compared to healthy controls. Methods: Consecutive autoimmune vasculitis patients fulfilling the aCR criteria and age and gender matched healthy controls were evaluated by NVC using Optilia Mediscope with a magnification of X200. Patients with peripheral artery disease and ischemic heart disease were excluded. Capillaroscopy images were centrally analyzed. NVC was analyzed, noting: architecture, number of capillaries per field, capillary width, capillary morphology, microhemorrhages, peri-capillary stippling (PCS)- hemosiderin deposits probably representing former capillary leak, slow capillary flow ("rolling" or sludging of red blood cells) and avascularity. Continuous data are presented as the mean ± SD. Categorical variables are presented as frequencies and percentages. Comparisons of continues variables were made using 2-tailed t-tests and differences between groups by a 1-Way aNOVA. Results: Seventeen patients with active vasculitis, 8 patients with vasculitis in remission (11 polyarteritis nodosum, 2 GPA, 3 eosinophilic granulomatosis with polyangiitis, 2 microscopic polyangiitis, 2 Takayasu, 3 Sjogren vasculitis (one with cryoglobulinemia), 1 primary central nervous system vasculitis and 1 lupus vasculitis) were compared to 25 age and sex matched healthy controls. The mean age (59 ±18 vs. 51±19 vs. 52±15), and the percent of females (53%, 50%, 60%), were similar between the groups. Patients with active vasculitis demonstrated higher rate of "rolling", 74.1%±27 vs. 12.5%±22 vs. 6.5%±12.7, p<0.001; microhemorrhages or PCS 30.1%±26.4 vs. 1.5%±4.5 vs. 1.9%±1, p<0.05, which reversely correlated with disease duration r=-0.4, P=0.05;avascular areas 76%±19.5 vs. 23.4%±28 vs. 26%±18.5, p<0.01 and neoangiogenesis 57%±23% vs 26.5%±22.5 vs. 6% ±10.5, p<0.01. PCS was observed exclusively in 5 of 17 patients with active vasculitis. Conclusion: Patients with active vasculitis demonstrate capillary abnormalities, namely: "rolling", microhemorrhages, avascular areas and neoangiogenesis. PCS may be a specific sign of active vasculitis. NVC is an easy, readily available additive tool in the management of vasculitis. Further studies are needed to ascertain the role of NVC in vasculitis. References: [1] Sendino Revuelta a, Barbado Hernández FJ, Torrijos Eslava a, González anglada I, Peña Sánchez de Rivera JM, Vázquez Rodríguez JJ. Capillaroscopy in vasculitis.An Med interna. 1991;8(5):217-20. Spanish. [2] HJ anders, C Headecke, T Sigl, K Kruger. Avascular areas on nailfold capillary microscopy of patients with Wegener's granulomatosis. Clin Rheumatol. 19:86-8, 2000 [3] aytekin S, Yuksel EP, aydin F, Senturk N, Ozden MG, Canturk T, Turanli aY. Nailfold capillaroscopy in Behçet disease, performed using videodermoscopy. Clin Exp Dermatol. 2014;39(4):443-7. [4] Javinani a, Pournazari M, Jamshidi aR, Kavosi H. Nailfold videocapillaroscopy changes in Takayasu arteritis and their association with disease activity and subclavian artery involvement. Microvasc Res. 2019;122:1-5 Disclosure of interests: None declared